Exploring factors affecting developer abandonment of open source software projects. Issue 9 (28th June 2022) - Kaur, Rajdeep; Chahal, Kuljit Kaur
Abstract: Open Source Software (OSS) projects have long been studied to understand the need of community support for their growth and survival. However, there has been limited research on developers' abandonment, though it is found to have detrimental effect on quality and sustainability of OSS projects. This paper examines the impact of developer and project‐related factors on developer abandonment in OSS projects. Factors include developer attributes: experience, role, coding language, and joining date, and project attributes: change complexity and sentiments in commit logs. The findings are (1) for developer experience, core/non‐core member, and joining date; there exists a pattern of developers abandoning the projects. (2) There is no definite answer for coding language. (3) It does not relate to the change profile of a project except a few indicators. Sentiments can also not be linked. These results provide OSS community and researchers with useful insights on developer abandonment and the factors influencing it or not. Abstract :